Difficulties of university students in oral expression - Gonzales Rodríguez, María Mercedes (2015)
One of the abilities required by several carriers in San Marcos University is oral expression. Professors manifest that students do not express properly, that is the reason why some carriers have considered the implementation, in their curricular system, of evaluation through oral expression- it means expositions- as a way of solving the problem. To deal with the mentioned problem in the course of Spanish (Lengua Española), we look into the difficulties that students present when they speak to an audience in the performance of a story. We analyze the answers given by students to questions that contrastthe difficulties they have between the familiar and electronic oral discursive practices and the requirement of the discursive practices of the university area.